1 Utwórz sumy algebraiczne o wyrazach.
A 5x, -7y, -xy, -4,
B -2a, -6a2 , 3ab, -b2
C 8ax, 2/3a, -0,2x, 9a2 ,
D 15, 4,5x, -3xy, -x y,
2 Wykonaj działania i przeprowadź redukcję wyrazów podobnych:
A (3x+5)+(7x-2y+6)+(-x+y-1)
B -(4a+2b-1)+(-3a-3b+4)-(6a+3)
C –[-(3x+2y)]-(-2x-2y)+(-5x-3y)
D6xy-(2xy+3y)+(-xy+4x-7y)
E (4a2 +3ab+b2 )-(-a2 -ab+b2 )-(4a2 -2b)
F (2a+5ab+3b)-(3a+5ab+1)-(-a+3b)

1

Odpowiedzi

2010-03-15T17:05:17+01:00
A 5x, -7y, -xy, -4,
5x-7y-xy-4
B -2a, -6a2 , 3ab, -b2
-2a-6a²+3ab-b²
C 8ax, 2/3a, -0,2x, 9a2 ,
8ax+2/3a-02x+9a²
D 15, 4,5x, -3xy, -x y,
15+4,5x-3xy-xy=15+4,5x-4xy

A (3x+5)+(7x-2y+6)+(-x+y-1) =
= 3x+5+7x-2y+6-x+y-1 =
= 9x-y+10
B -(4a+2b-1)+(-3a-3b+4)-(6a+3) =
= -4a-2b+1-3a-3b+4-6a-3 =
= -13a-5b-2
C –[-(3x+2y)]-(-2x-2y)+(-5x-3y) =
= -(-3x-2y) + 2x+2y-5x-3y =
= 3x+2y-3x-y =
= y
D6xy-(2xy+3y)+(-xy+4x-7y) =
= 6xy-2xy-3y-xy+4x-7y=
= 3xy-10y+4x
E (4a2 +3ab+b2 )-(-a2 -ab+b2 )-(4a2 -2b)=
= 4a²+3ab+b²+a²+ab-b²-4a²+2b=
= 4ab+a²-b²+2b
F (2a+5ab+3b)-(3a+5ab+1)-(-a+3b)=
= 2a+5ab+3b-3a-5ab-1+a-3b =
= -1
3 3 3